Realisasi Sabar dalam Menjalani Keseharian: Studi Hadis - Anggita Yuliandra; Busro; Abdul Syukur (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about patience. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about patience in the history of al-Bukhari no. 5220. The results and discussion of this study indicate that the status of the hadith is hasan li ghairihi and even authentic with the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by al-Bukhari no. 5220 is relevant to be used as a sprit of patient realization in living daily life.